VD_FINDINFO Jug / 2016 / 95 vom 11. November 2015 - VD Tribunal cantonal (2015)
PRÉSOMPTION D'INNOCENCE, VIOLATION DE DOMICILE, DÉTÉRIORATION DE DONNÉES | 126 CP, 143bis CP, 144bis CP, 180 CP, 186 CP, 10 CPP (CH)